Evolution and importance of Molecular Microbiology in the Laboratory of the Provincial Center for Hygiene, Epidemiology and Microbiology - María de Lourdes Sánchez Alvarez; Rafael Abreu Duarte; Edenis García Alvarez; Adrian Fernández García; Ermis Alexander González Martínez; Maidelys Mendoza Acosta (Acta Médica del Centro)
Introduction: the need to have rapid, sensitive and specific laboratory techniques for the detection of pathogens that are difficult to diagnose led to the creation of the Molecular Biology Laboratory at the Provincial Center of Hygiene, Epidemiology and Microbiology of Villa Clara. Objective: to characterize the evolution and importance of Molecular Microbiology in the Laboratory of the Provincial Center of Hygiene, Epidemiology and Microbiology of Villa Clara from June 2018 to December 2023. Methods: cross-sectional descriptive study carried out at the Villa Clara Molecular Biology Laboratory in the period from June 2018 to December 2023 based on the total samples processed by polymerase chain reaction, several technological platforms and various kits were used. commercial. Results: In 2018, molecular diagnosis was implemented with two platforms, Rotor Gene-Q® and Gene Xpert® MTB/RIF, and in 2021, four were available, when the SLAN and the COBAS 4800® platform were introduced. The laboratory became relevant due to the arrival of the 2019 new coronavirus pandemic: 511,225 nasopharyngeal exudate samples and 14,568 determinations were processed for the diagnosis of human immunodeficiency viruses, hepatitis C and B, and human papilloma carried out on the COBAS 4800® platform. In 2023, the pathogen detection capacity was strengthened and the community cocirculation of influenza A and B, parainfluenza virus type 4, the OC 43 coronavirus, SARS-CoV-2 and dengue was identified. Conclusions: the progressive increase in the resolution capacity of the Molecular Biology Laboratory, together with the implementation of new diagnostic platforms, has allowed us to strengthen the detection of pathogens of clinical interest and improve virological sentinel surveillance.